ANALISIS SISTEM PEMANCAR PADA PT. MEDIA KHATULISTIWA TELEVISI/ KOMPASTV PONTIANAK - Eko Prasetyo Manalu . (Faculty of Engineering, Universitas Tanjungpura, 2016)
Television Station PT. Media Khatulistiwa Televisi or more known KompasTV Pontianak is one of the television transmitter located on Pontianak city. Television Station Pontianak KompasTV located at coordinates -0°01'766” southern latitude 109°20'145” east longitude which is located at the 3rd floor of the Kompas Gramedia Building at Hos Cokroaminoto Number 56 Pontianak, West Kalimantan. Kompas television station transmitting antenna Pontianak located at the rear of the building whose height reach 62 meters above the ground, operate on channel 39 using frequency 615.25 MHz. Antenna transmit power belongs Pontianak television companies is 1000 watt with 8 panels transmitting that located upper tower which each direction consists of two panels where direction to North 0o, West 90o, South 180o and East 270o. The number of panels 8 units be expected can make clear the broadcasts in terms of both image and sound. The calculations that the maximum range of the transmitting antenna KompasTV Pontianak Station is 15 km, as for the analysis of reception quality video and audio authors conducted a study testing the use directly to the people who use the television which use yagi antenna as an antenna that use a broadcast signal receiver and see firsthand the quality of the video and audio are received. After conducting research and trials, limit the maximum range of very good quality and a good KompasTV television station covers an area of northern region: Budi Utomo (5,1 km), Batu Layang (5,6 km), and Wajok Hulu (11,1 km). Eastern region: Tanjung Hulu (4,6 km), Parit Aim(8,6 km) and Jawa Tengah Ambawang (13,1 km), southern region: Parit Haji Husein 2 (5,3 km), A.Yani 2 (9,4km) and Desa Limbung (14,8 km). And western region: Pal 9 (6,1 km) and Jl. Raya Sungai Kakap (10,2 km). Keyword- Television, transmitter, KompasTV Pontianak, Antenna, Quality of Vision and Sound.